UN-ACCOUNTABLE POLITICAL PARTY XYZ: IS THE BRIDGE TOWARDS CORRUPTION? - Salmah, St; Irianto, Gugus; Mulawarman, Aji Dedi; Purwanti, Lilik (The International Journal of Accounting and Business Society, 2021)
Purpose — This study aims to reconstruct the concept of public accountability that is free from the lifeworld colonization which is carried out by the concept of the New Public Management.Design/methodology/approach — Problem-solving in this study will be approached through the critical perspective of Habermas (Gallhofer & Haslam, 1996); (Oakes & Oakes, 2016); (Gallhofer & Haslam, 2015). The critical perspective of Habermas will reveal the lifeworld colonization of accountability for the cadre of political parties XYZ, public discussion space is the main problem in this study.Findings — The findings of this study are that the accountability of cadre, seen from the process of implementing cadre, has eroded its meaning. That is the instant cadre process by relying on the financial strength and the strong oligarchy of capital leadership in political parties XYZ which is a bridge to corruption. The loss of the meaning of the nature of political parties as an institution given the mandate to fight for the interests of the welfare and sovereignty of the people because of the dominance of the interests of political party elites. Un-accountable cadre political party XYZ due to the thick transactional politics in the cadre process is a trigger for distrust of the public to political party XYZ. Accountability of the cadre seems to ignore deliberations in the public discussion room, both legislative and executive elections, hence corruption scandals are increasing in Indonesia.Practical Implications — This study emphasizes the accountability of cadres who are oriented to the process of recruiting political party cadres. Originality/value — This study uses the critical perspective of Habermas. Through the Habermas approach, the researcher wanted to understand the lifeworld colonization of cadre accountability that occurs in the community. Related to the cadre accountability issue, the hegemony of public discussion rooms is the main issue.Keywords Un-Accountable, Political Parties, Transactional Politics, Corruption, HabermasPaper Type Research Paper.